The dominant mechanisms for the formation of solute-rich clusters in low-Cu steels under irradiation. (September 2020) - Castin, N.; Bonny, G.; Bakaev, A.; Bergner, F.; Domain, C.; Hyde, J.M.; Messina, L.; Radiguet, B.; Malerba, L.
Abstract: The formation of nano-sized, coherent, solute-rich clusters (NSRC) is known to be an important factor causing the degradation of the macroscopic properties of steels under irradiation. The mechanisms driving their formation are still debated. This work focuses on low-Cu reactor pressure vessel (RPV) steels, where solute species are generally not expected to precipitate. We rationalize the processes that take place at the nanometer scale under irradiation, relying on the latest theoretical and experimental evidence on atomic-level diffusion and transport processes. These are compiled in a new model, based on the object kinetic Monte Carlo (OKMC) technique. We evaluate the relevance of the underlying physical assumptions by applying the model to a large variety of irradiation experiments. Our model predictions are compared with new experimental data obtained with atom probe tomography and small angle neutron scattering, complemented with information from the literature. The results of this study reveal that the role of immobilized self-interstitial atoms (SIA) loops dominates the nucleation process of NSRC. Graphical abstract: Image 1 Highlights: Formation of solute-rich clusters is responsible for ferritic steels hardening and embrittlement. Theoretical and experimental evidence suggest that their formation is driven by self-interstitial defects. This work compiles all evidence and demonstrates the role of self-interstitial defects. Development of an object kinetic Monte Carlo model for solutes-rich clusters formation (Cu, Mn, Ni, Si, P) in ferritic steels under irradiation.